2019
DOI: 10.1002/cncr.32477
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress is associated with a higher symptom burden in cancer survivors

Abstract: Background Although multiple co‐occurring symptoms are a significant problem for cancer survivors, to the authors' knowledge little is known regarding the phenotypic characteristics associated with a higher symptom burden. The objectives of the current study were to evaluate the occurrence, severity, and distress associated with 32 symptoms and examine the phenotypic and stress characteristics associated with a higher symptom burden. Methods A total of 623 cancer survivors completed a demographic questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 49 publications
(77 reference statements)
3
33
0
Order By: Relevance
“…Epidemiology studies corroborate the bidirectional relationship between pain and insomnia, where pain affects sleep onset and maintenance, and sleep impairments may further exacerbate pain 6,7 . Pain and insomnia also contribute to the progression of fatigue and mental distress that further worsen symptom burden, leading to poor quality of life [8][9][10] . In breast cancer patients, pain and psychological symptoms like insomnia and depression are associated with early discontinuation and non-adherence to adjuvant hormonal therapy and, consequently, poor clinical prognosis [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiology studies corroborate the bidirectional relationship between pain and insomnia, where pain affects sleep onset and maintenance, and sleep impairments may further exacerbate pain 6,7 . Pain and insomnia also contribute to the progression of fatigue and mental distress that further worsen symptom burden, leading to poor quality of life [8][9][10] . In breast cancer patients, pain and psychological symptoms like insomnia and depression are associated with early discontinuation and non-adherence to adjuvant hormonal therapy and, consequently, poor clinical prognosis [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, patients also endorsed a perceived improvement in appetite (21 of 39, 53.8%) and pain (14 of 39, 35.9%). It is well known that despite the advancements in interventions targeting symptom management, cancer survivors continue to deal with a high burden of symptoms ( 18 ). In a large retrospective study that included 4,903 cancer survivors, 4,512 patients (92%) reported having symptoms related to their cancer or anti-cancer therapy 1 year after therapy ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive statistics, including frequencies, means, standard deviations, and ranges, were used to summarize all sociodemographic and disease-related characteristics and measure responses. To determine depressive symptom severity groups, established cut-offs for the PHQ-9 were used [33]: none/mild (1-7), moderate (8)(9)(10)(11)(12)(13)(14), and severe (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Analyses tested the hypothesis that overall group differences would be found, with negative functioning/symptoms outcomes ordered such that severe > moderate > none/mild.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analytic study revealed stress assessed at some time after lung cancer diagnosis to heighten risk for premature cancer death (n = 23 studies; hazard ratio = 1.17; 95 % CI = 1.03-1.34) [20]. Potential contributors to the latter effects are the covariation of heightened stress with physical symptom exacerbation [21][22][23][24][25][26] and depressive symptoms [23,27].…”
Section: Introductionmentioning
confidence: 99%